2020
DOI: 10.3390/jpm10040240
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Home Monitoring Application for Follow Up after Lung Transplantation—A Pilot Study

Abstract: Home spirometry after lung transplantation is common practice, to monitor graft function. However, there is little experience with online home monitoring applications with direct data transfer to the hospital. We evaluated the feasibility and patient experiences with a new online home monitoring application, integrated with a Bluetooth-enabled spirometer and real-time data transfer. Consecutive lung transplant recipients were asked to evaluate this home monitoring application for three months in a pilot study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…However, in other studies with a similar methodology, higher percentages of compliance with home spirometry were obtained, mostly above 90% [ 13 , 14 , 15 , 16 ]. In one pioneering study from 2017, adherence to home spirometry was observed to decrease over time [ 9 ], and the same was seen in several studies following lung transplant patients [ 5 ] or patients with Duchenne Muscular Dystrophy [ 30 ]. One of the potential reasons for this result, as well as for the slightly lower-than-expected compliance rate in our study, is that some patients forgot to perform the spirometry every day, with the majority of them being elderly and unfamiliar with the daily use of modern technology.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…However, in other studies with a similar methodology, higher percentages of compliance with home spirometry were obtained, mostly above 90% [ 13 , 14 , 15 , 16 ]. In one pioneering study from 2017, adherence to home spirometry was observed to decrease over time [ 9 ], and the same was seen in several studies following lung transplant patients [ 5 ] or patients with Duchenne Muscular Dystrophy [ 30 ]. One of the potential reasons for this result, as well as for the slightly lower-than-expected compliance rate in our study, is that some patients forgot to perform the spirometry every day, with the majority of them being elderly and unfamiliar with the daily use of modern technology.…”
Section: Discussionmentioning
confidence: 84%
“…However, one of the basic questions that needed to be addressed at the start of the use of home spirometers was the reliability of the results obtained, in comparison to those obtained during office-based spirometry. In a large number of studies conducted thus far, it was determined that there are no statistically significant differences in the values of parameters measured during spirometry in office and home conditions [ 5 , 13 , 14 , 15 , 16 , 27 ]. According to the findings of our study, there were no statistically significant differences between FVC values at the beginning and end of the study for both office- and hospital-based spirometry, with a statistically significant positive correlation between them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations